CLEAN AND HEALTHY LIVING BEHAVIOR AND THE INCIDENCE OF DENTAL CARIES IN SCHOOL-AGED CHILDREN - Siti Rukhaniyah; Umi Faridah; Muhamad Jauhar (Universitas Muhammadiyah Kudus, 2025)
Dental and oral health has become a problem that needs to be solved immediately. In Indonesia, the prevalence of dental caries tends to be high (above 70%) in all age groups. There is an improvement in the prevalence of dental caries in school-aged children. This happened because the children did not exhibit healthy hygiene. To determine the relationship between clean and healthy living behavior and the incidence of dental caries in school-aged children. Correlational analytical research type. Cross-sectional approach method. The research variable studied was dental caries. The population of all students at Pecangaan Elementary School Jepara is 80 students. By using the Slovin formula, the final result is 45 students. The research sample was selected based on the inclusion criteria: 1) Having dental caries. 2) Children aged 6-12 years at Pecangaan Elementary School. 3) Willing to be a respondent. Exclusion criteria: 1) Children who were not present during the research. 2) Children who do not agree to informed consent. A stratified random sampling was used to determine the sample for each class. The measuring tool used is a